Game Mohares Sebagai Media Memperkenalkan Makanan Sehat Pada Anak - Nagari, Annisa Rahayu Bekti; Sutanto, Teguh; Nurcahyawati, Vivine (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Children in group 6-12 years old are susceptible to food consumption. They tend to be rare consume healthy food and the recommended ones. Causes other than not knowing parents to wise of healthy food choosen also they are who tend to their food preferences. According to RISKESDAS (2013), consumption trends child eat less of vegetables and fruit in a week reach 90.5% only to the area East Java. To find out how to introduce healthy food to the children’s age, then made observations at kindergarten and elementary school the city of Surabaya. At the kindergarten the way of introduced healthy food through centra cooking while at elementary school there are uses thematic books base of curriculum, but the content both that way still lack of the material being taught. Base of case above there is a game with genre casual education base of 2D for Android. This game design full of content about vegetables, fruits and side dishes and carbohidrates. From the test results of the application the user questionnaire obtained an increase of 2.3% after using Mohares gaming applications. Keywords: children, healthy food, game, android.